Modulated model predictive control for a 7-level cascaded h-bridge back-to-back converter - Tarisciotti, Luca; Zanchetta, Pericle; Watson, Alan James; Bifaretti, Stefano; Clare, Jon C. (IEEE, 2014)
Multilevel Converters are known to have many advantages for electricity network applications. In particular Cascaded H-Bridge Converters are attractive because of their inherent modularity and scalability. Predictive control for power converters is advantageous as a result of its applicability to discrete system and fast response. In this paper a novel control technique, named Modulated Model Predictive Control, is introduced with the aim to increase the performance of Model Predictive Control. The proposed controller address a modulation scheme as part of the minimization process. The proposed control technique is described in detail, validated through simulation and experimental testing and compared with Dead-Beat and traditional Model Predictive Control. The results show the increased performance of the Modulated Model Predictive Control with respect to the classic Finite Control Set Model Predictive Control, in terms ofcurrent waveform THD. Moreover the proposed controller allows a multi-objective control, with respect to Dead-Beat Control that does not present this capability.